Plasma‐assisted molecular beam epitaxy growth diagram of InGaN on (0001)GaN for the optimized synthesis of InGaN compositional grades. Issue 4 (26th February 2016) - Hestroffer, Karine; Lund, Cory; Li, Haoran; Keller, Stacia; Speck, James S.; Mishra, Umesh K.
Abstract: A PAMBE (plasma‐assisted molecular beam epitaxy) growth diagram of InGaN is established for the metal‐face (0001) orientation at 575 °C. This growth diagram allows identifying different growth regimes during the epitaxy of InGaN, namely the N‐rich, the Ga‐rich, the intermediate In‐rich, and the In‐accumulation regimes. InGaN compositional grades are then grown by ramping the Ga and In fluxes in parallel to remain in either the intermediate In‐rich or the N‐rich regime. The two samples exhibit distinct structural characteristics, surface morphologies, and optical properties. The growth diagram proves to be a useful tool in controlling the metal fluxes and thereby the stoichiometry conditions on the surface during the growth of compositionally graded layers.